1997
DOI: 10.1080/00984109708984061
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Evaluation of Petroleum Blending Streams: Reproductive and Developmental Effects of Hydrodesulfurized Kerosine

Abstract: Hydrodesulfurized kerosine (HDS kerosine), applied dermally, was tested for reproductive and developmental toxicity in Sprague-Dawley rats, using a modified OECD Guideline 421, Reproductive/Developmental Toxicity Screening Protocol. A preliminary acute dermal irritancy test demonstrated that dilution of HDS kerosine in either a light (100 Saybolt universal seconds, SUS) or moderate viscosity (340 SUS) USP mineral oil reduced irritation of the neat material comparably. Similar dermal absorption was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In a study carried out according to OECD Test Guideline 421 in SD rats, no relevant effects on reproduction were found compared with untreated control animals after dermal application of 1 ml white mineral oil/kg body weight and day (about 850 mg/kg body weight) (Schreiner et al 1997).…”
Section: Fertilitymentioning
confidence: 97%
“…In a study carried out according to OECD Test Guideline 421 in SD rats, no relevant effects on reproduction were found compared with untreated control animals after dermal application of 1 ml white mineral oil/kg body weight and day (about 850 mg/kg body weight) (Schreiner et al 1997).…”
Section: Fertilitymentioning
confidence: 97%
“…A series of studies (Schreiner et al, 1997(Schreiner et al, , 1998(Schreiner et al, , 2000 investigate d the toxicity of repeated exposure to light catalytic reformed naphtha (LCRN) distillate, a major blending component of unleaded gasoline containing up to 10% (v/v) benzene. LCRN (C5-C11) is produced at over 25 million gallons/yr in the United States, and constitutes up to 30% of unleaded gasoline.…”
Section: Hydrocarbon Fuel Neurotoxicity 273mentioning
confidence: 99%
“…In addition, several reproductive and developmental toxicity studies using low viscosity mineral oils as a solvent control are available (Schreiner et al, 1997;McKee et al, 1987a;McKee et al, 1987b). In 2009, EFSA reviewed these studies and concluded that, although there are no specific reproductive or developmental toxicity studies of high viscosity mineral oils, the studies performed with low viscosity white mineral oils are useful in providing evidence of the lack of reproductive or developmental effects of white mineral oils.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%